(untitled) (London,New York, 1998)
This newly revised clearly-presented text looks at Japan's economic history from the nineteenth century through to World War II. Within a framework based on the theories and approaches of Development Studies, it demonstrates the relevance of Japan's pre-war experience to the problems facing developing countries today, and draws out the historical roots of the institutions and practices on which Japan's post-war economic miracle was based. New features include: · fresh theoretical perspectives · additional material derived from new sources · increased number of case studies · fully up-dated references and bibliography. This broad-ranging textbook is both topical and easy-to-use and will be of immense use to those seeking an understanding of Japanese economic development.
Keywords: Development economics,Phát triển kinh tế; Japan,Nhật Bản